Comparative Analysis of Data Warehousing Solutions in the Cloud: A Focus on Azure PostgreSQL - Mahesh Thoutam (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article provides a comprehensive analysis of cloud data warehousing solutions, with a focus on Azure PostgreSQL. It examines the rapidly growing cloud data warehouse market, highlighting key advantages such as scalability, cost-effectiveness, and advanced analytics capabilities. The article compares major platforms including Azure PostgreSQL, Amazon Redshift, Google BigQuery, and Snowflake, detailing their features, strengths, and market positions. Special attention is given to Azure PostgreSQL, outlining scenarios where it excels and providing best practices for leveraging its features. The analysis aims to guide decision-makers in selecting the most suitable cloud data warehousing solution for their specific business needs in an evolving data management landscape.